Modeling Of The Thermal Behavior Of Metals During Welding Laser Using Beam - Lemkeddem, S.; Khelfaoui, F. (University of Eloued جامعة الوادي, 2012)
The laser welding provides a very high energy density, this allows the use of welds narrow, deep and at high speeds. Because of its advantages over other joining processes, laser welding is a process of manufacturing the most important. In order to model the thermal behavior, we must study the different phenomena that may be involved in the operation. The temperature distribution in the workpiece can be determined from the heat equation which expresses the energy balance. This is a parabolic differential equation and for resolution we applied the finite difference method using the implicit scheme.
Articale in Journal of fundamental and Applied Sciences Vol. 04 N. 01
Keywords: Laser Welding, Metal, Finite differences, temperature profile.